1971
DOI: 10.1002/cpt1971126955
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of prognosis and response to an imidazole carboxamide in malignant melanoma

Abstract: In a prospective randomized study of 155 patients, dimethyltriazeno imidazole carboxamide, 2.0 or 4.5 mg. per kilogram given for 10 successive daily intravenous doses, resulted in ob;ective response in 28 per cent of 115 evaluable patients. The 2.0 mg. schedule produced a significantly greater rate and duration of response (p S; 0.05) than did the 4.5 mg. schedule. In half of the responding patients the response exceeded 6 months in duration. Urinary melanogens, detected by a qualitative test in 29 per cent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1972
1972
1988
1988

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Einhorn and co‐workers (1974) reported that patients with non‐visceral disease respond much better to DTIC than do patients with visceral (lung, liver, brain) metastases. The studies of Johnson and Jacobs (1971) and Nathanson et al (1971) have shown that DTIC has a greater effect in females than in males. On the negative side, Hill et al (1974) studied 107 patients after surgery for malignant melanoma by random assignment to receive or not to receive DTIC.…”
Section: Section 18amentioning
confidence: 94%
See 2 more Smart Citations
“…Einhorn and co‐workers (1974) reported that patients with non‐visceral disease respond much better to DTIC than do patients with visceral (lung, liver, brain) metastases. The studies of Johnson and Jacobs (1971) and Nathanson et al (1971) have shown that DTIC has a greater effect in females than in males. On the negative side, Hill et al (1974) studied 107 patients after surgery for malignant melanoma by random assignment to receive or not to receive DTIC.…”
Section: Section 18amentioning
confidence: 94%
“…There was a greater response rate in women than in men (54%: 17%). Similarly, the studies of Johnson and Jacobs (1971) and Nathanson et al (1971) have shown that systemic administration of DTIC also has a better effect in women than in men. These investigators found that the toxicity of DTIC by infusion was less than by systemic administration.…”
Section: Section 18bmentioning
confidence: 97%
See 1 more Smart Citation
“…Responded consistently outlive nonresponders, but no definite proof exists suggesting an overall survival benefit for treated patients, since most studies do not compare treated patients with untreated controls. Doses and schedules do not appear to affect response rate as much as they affect toxicity, which is (for DTIC) severe nausea and vomiting, diarrhea, moderate myelosuppression, and a peculiar influenza‐like syndrome of fever, myalgia, and malaise. To date, no other well‐studied agent or combination of agents matches the therapeutic record of DTIC, modest as that record is.…”
Section: Single‐agent Chemotherapymentioning
confidence: 99%
“…The decrease in DTIC dose is unlikely to be responsible for this; in fact, in the treatment of melanoma a dose of 2 mg/kg DTIC per day for 10 days produced a significantly greater response rate than 4.5 mg/kg/day for 10 days [18] (2 mg/kg/day for 10 days produces a similar total dose as 150 mg/m2/day for 5 days). It is possible that the increase in Adriamycin dose to 60 mg/m2 was not enough and doses in the range of 70-80 mg/m2 arc needed to achieve the desired increase in response as shown in several of the series quoted [5,14], Presant ct al.…”
Section: Toxicitymentioning
confidence: 99%